2016
DOI: 10.1051/matecconf/20165801007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Calcium Additive on the Crystallization of Struvite

Abstract: Crystallization of struvite [MgNH4PO4.6H2O] may lead to the deposition of scale which may create significant problems in the process pipes, pumps and other industrial equipment. However, struvite precipitation can be benefited for phosphate recovery for use of fertilizer. The aim at the present work was to investigate calcium additive on struvite precipitation. The experiment was carried out in a batch mode using a 1-liter Pyrex glass vessel mechanically agitated for 200 rpm. The scale-forming solution was pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
(13 reference statements)
0
3
0
Order By: Relevance
“…The molar ratio of Ca and K in syngenite based on EDX analysis for additional magnesium doses of 5 mmol/l, 10 mmol/l and 15 mmol/l at pH 11.0 were 1:2.1, 1:2.8 and 1:3.2 respectively with the best %K and %Ca are 42% and 31%. The phosphate value in this study is also quite high, because besides being able to react with syngenite, calcium ions can also actively react with phosphate to form calcium phosphates [24].…”
Section: Effect Of Increasing Ph and Mg Dosages In The Syngenite Formationmentioning
confidence: 71%
See 1 more Smart Citation
“…The molar ratio of Ca and K in syngenite based on EDX analysis for additional magnesium doses of 5 mmol/l, 10 mmol/l and 15 mmol/l at pH 11.0 were 1:2.1, 1:2.8 and 1:3.2 respectively with the best %K and %Ca are 42% and 31%. The phosphate value in this study is also quite high, because besides being able to react with syngenite, calcium ions can also actively react with phosphate to form calcium phosphates [24].…”
Section: Effect Of Increasing Ph and Mg Dosages In The Syngenite Formationmentioning
confidence: 71%
“…However, in the study only Ca and K, the S ion can not identified as crystals formed because these minerals may precipitate in the order of days and are influenced by the pH of the solution and the concentration of magnesium and phosphate [24]. The molar ratio of Ca and K in syngenite based on EDX analysis for additional magnesium doses of 5 mmol/l, 10 mmol/l and 15 mmol/l at pH 11.0 were 1:2.1, 1:2.8 and 1:3.2 respectively with the best %K and %Ca are 42% and 31%.…”
Section: Effect Of Increasing Ph and Mg Dosages In The Syngenite Formationmentioning
confidence: 93%
“…The vessels with single [89] mechanical agitator or multiple agitators systems are often used in various configurations in three-phase or two-phase mixing processes [90], such as catalysed oxidation, polymerisation, evaporative crystallization [91], aerobic fermentation, [92] froth flotation [93], flocculation [94], microbial coal desulphurisation, gold leaching, bacterial, sulphide oxidations or separation processes etc. In all these applications, simultaneous dispersion of gas and the suspension of the solids have crucial meaning.…”
Section: A Solid-liquid System In a Mechanically Agitated Vesselmentioning
confidence: 99%